Stiffness gradient of the beetle penis facilitates propulsion in the spiraled female spermathecal duct - Filippov, Alexander E. (Sci Rep, 2016)
It is well known that sexual selection is the main driving force of substantial diversity of genitalia found in animals. However, how it facilitates the diversity is still largely unknown, because genital morpho/physical features and motions/functional morphology of the structures in sexual intercourse are not linked for the vast majority of organisms. Here we showed the presence of material gradient and numerically studied an effect of stiffness gradient of the beetle penis during its propulsion through the female duct. We found that stiffness gradient on the penis essentially affects its propulsion. Microscopic investigation suggests the possibility that the tip of the hyper-elongated penis is softer than the rest of it, and our numerical model confirms that this type of distribution of stiffness gradient aids in faster propulsion than other types. This result indicates that previously ignored physical properties of genital materials are of crucial importance in evolutionary studies of genitalia.